The persistent problem of late HIV diagnosis in people with AIDS: a population-based study in Italy, 1999–2013. (January 2017) - Taborelli, M.; Virdone, S.; Camoni, L.; Regine, V.; Zucchetto, A.; Frova, L.; Grande, E.; Boros, S.; Dal Maso, L.; De Paoli, P.; Serraino, D.; Suligoi, B.
Abstract: Objectives: Despite the wide accessibility to free human immunodeficiency virus (HIV) testing and combined antiretroviral therapy (cART), late HIV diagnosis remains common with severe consequences at individual and population level. This study aimed to describe trends of late HIV testing and to identify their determinants in the late cART era in Italy. Study design: We conducted a population-based, nationwide analysis of the Italian National AIDS Registry data (AIDS – acquired immune deficiency syndrome) for the years 1999–2013. Methods: Late testers (LTs) were defined as people with AIDS (PWA) whose first HIV-positive test preceded AIDS diagnosis by 3 months or less. Odds ratios (ORs) with the corresponding 95% confidence intervals (CIs) were estimated to examine factors associated with being LTs. Joinpoint analysis was used to estimate annual percent changes (APCs) of LTs' proportion over time. Results: Among 20, 753 adult PWA, 50.8% were LTs. Italian PWA showed a lower proportion of LTs than non-Italian PWA (46.5% vs 68.2%). Among Italian PWA, the odds of being LTs was higher in men than in women (OR = 2.62, 95% CI: 2.38–2.90); in the age groups below 35 years and over 49 years at diagnosis (OR = 1.24, 95% CI: 1.12–1.37 and OR = 1.51, 95% CI: 1.38–1.67, respectively) vs PWA aged 35–49 years; and in those infected through sexual contact as compared with injecting drug use (OR = 13.34, 95% CI: 12.06–14.76 for heterosexual contact and OR = 8.13, 95% CI: 7.30–9.06 for male-to-male sexual contact). The proportion of LTs increased over time among Italians, especially in the latest period (APC2006–2013  = 5.3, 95% CI: 3.8–6.9). The LTs' proportion resulted higher, though stable, among PWA aged ≥50 years. Conversely, an increasing trend was observed among PWA aged 18–34 years (APC = 5.3, 95% CI: 4.5–6.1). The LTs' proportion was persistently higher among PWA who acquired HIV infection through sexual contact, even if a marked increase among injecting drug users was observed after 2005 (APC = 11.4, 95% CI: 5.7–17.5). Conclusions: The increasing trend of LTs' proportion in the late cART era highlights the need of new strategies tailored to groups who may not consider themselves to be at a high risk of infection. Active promotion of early testing and continuous education of infection, especially among young people, need to be implemented. Highlights: Half of people diagnosed with AIDS in Italy are late HIV testers (LTs). Gender, age at diagnosis and HIV transmission mode are associated with late testing. The LTs' proportion increased over time, especially among Italians aged 18–34 years. A marked increase of LTs' proportion emerged after 2005 among injecting drug users. Promotion of HIV testing, especially among young people, needs to be implemented.